Peningkatan Nilai Ekonomi Berbasis Produk Lokal Bagi Mama-mama Asli Papua di Dusun Sarsang - Valentina Simorangkir, Yosi; Nurhuzna, Atiza (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2023)
This study aims to enhance the skills and knowledge of indigenous Papuan women in the production of banana saleh through socialization and training. Banana saleh is a local product with high economic potential, yet its production process is not fully mastered by the local community. This research employs a qualitative method, including observation, interviews, and practical training.The training results demonstrated a significant improvement in participants' knowledge and skills. Prior to the training, only 20% of participants had a good understanding of banana saleh production techniques, whereas after the training, 90% of participants could identify key steps and 85% were able to apply the taught techniques. Despite these improvements, challenges such as limited access to raw materials, equipment, and marketing still need to be addressed. Proposed solutions include sourcing raw materials, providing equipment, and developing local marketing strategies.The study concludes that community-based training involving hands-on methods effectively improves skills and knowledge. Ongoing support and appropriate strategies are necessary to ensure the program's sustainability and long-term benefits for Papuan women. With the recommended additional steps, it is hoped that banana saleh production can positively contribute to the economic well-being of the local community.